Índices climáticos globais e seus impactos regionais na Precipitação da Amazônia Oriental no início da estação chuvosa - MENEZES, José Felipe Gazel (2019)
This work aimed to describe the influence of the atmospheric and oceanic indexes on a region of the Eastern Amazon, in the months that represent the beginning of the rainy period of the Amazon, December, January and February. Atmospheric and oceanic index data were obtained from NOAA (National Oceanic and Atmosferic Administration), as well as time series, were studied in the Global Average temperature, SOI (Southern Oscillation Index), MEI (Multivariate ENSO Index), NOI (Northern Oscillation Index), TNA (Tropical Northern Atlantic Index), TSA (Tropical Southern Atlantic Index), PWP (Pacific Western warm pool), NINO (ENOS), NAO (North Atlantic Oscillation), PNA (Pacific North American Index) and WPI (Western Pacific Index) indexes, plotted their respective locations with the aid of the Grads software and a statistical correlation of Pearson Twofold, thus allowing to analyze the impacts of each index on the regime of rains in the Eastern Amazon, on an optic that different indexes have different impacts on an Amazon, being able to Contribute or to prejudice the regime of the region's rainfall, among the main results, to highlight the constant monitoring of the indexes studied, since the effects caused by large social, environmental and economic impacts, due to the low degree of infrastructure that a population Amazon has.